The use of guided discovery learning method to improve participation in answering reading comprehension questions - Firmansyah Firmansyah; Ikhsanudin Ikhsanudin; Clara Sadra (English, 2021)
This research was done by using Classroom Action Research method to solve the problems faced by the students. This research was conducted to the eleventh Grade Students of SMA Boedi Oetomo Pontianak in academic year of 2017/2018. Here, the researcher used purposive sampling as the sampling technique by choosing eleventh grade which consisted of 26 students. Techniques of data collecting were observation technique and measurement. To analyze the data, the researcher used qualitative and quantitative analyses. In qualitative data analysis, the researcher analyzed the displayed data, and drawing conclusion. While in quantitative data analysis, the researcher analyzed the data from the test which calculated by percentage of the students’ participation during each cycle in three cycles. In the initial cycle, the students’ participation was 21.30%. Meanwhile in the second cycle, the participation of the students was 45.62%. In the last cycle, the students’ participation was 60.60%. The researcher concluded that Discovery learning method was effective in improving the students’ participation in responding to the teacher’s questions. Therefore,discovery learning method could help the teacher in teaching and learning process because this method encouraged students to learn actively.